Can We Just Start Over Again? Resetting Remote Team Dynamics - Whiting, Mark E.; Bernstein, Michael S. (2020)
ABSTRACT Interactions defining teamwork today are heavily influenced by constraints and expectations found in in- person teams, however, remote collaboration provides the opportunity to try new ways to make teams work. One foundation of teamwork is persistent identity — we are who we were last time we worked together. Breaking with the expectation of in-person teams, we present a system that affords discontinuous identity using two-way pseudonym masking — enabling teams with new behaviors to arise from the same group of individuals. With this scaffold, a novel family of experiments, comparing the same group across multiple fresh starts, are possible. Further, interventions that involve choosing between versions of the same team are unlocked. We present an overview of experiments and interventions leveraging this system, and propose methods for its broader use in organizations enacting the future of work. Keywords remote teams, remote collaboration, identity, pseudonym masking ABOUT THE AUTHOR/S Mark E. Whiting University of Pennsylvania markew@seas.upenn.edu Mark (whiting.me) is a postdoc under Duncan Watts in both CIS in Engineering, OID at Wharton at U Penn. He holds bachelor’s and master’s degrees in Industrial Design from RMIT and KAIST respectively, a PhD in Mechanical Engineering from CMU, and a previous postdoc in HCI from Stanford. Michael S. Bernstein Stanford University msb@cs.stanford.edu Michael (hci.stanford.edu/msb) is an Associate Professor of Computer Science and STMicroelectronics Faculty Scholar at Stanford University, where he is a member of the HCI group. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).